Experimental and Numerical Investigations of Glued Cross-Laminated Timber Beams Produced with Different Wood Species and Glues - Ramazan Bülbül; Hakan Keskin; Musa Kaya; Omer Mercimek; Abdullah Türer; İrfan Kocaman; Minel Ahu Kara Alaşalvar; Yağmur Kopraman (BioResources)
Five-layer cross-laminated timber (CLT) beams made from 17-mm thick lumber pieces were produced using wood from Scots pine (Pinus sylvestris L.), Uludağ fir (Abies bornmüelleriana Mattf.), and oak (Quercus petraea L.). The outer layers consisted of Scots pine and oak, while the intermediate layers included Scots pine and fir wood. During the layer formation phase in the side-by-side joining press and in the CLT beam formation phase with layers stacked at 90°, polyvinyl acetate (PVAc) and polyurethane (PUR) adhesives were used. After conditioning the CLT beams at 20 °C and 65% relative humidity, their dry density values and results from a four-point bending test perpendicular to the adhesive line, including max load, displacement at max load, stiffness, max displacement, and energy dissipation capacity, were evaluated and compared with those obtained using ABAQUS finite element software. The results revealed that timber species, adhesive type, and perforation significantly influenced the mechanical behavior of CLT beams, with oak-based specimens generally outperforming fir and pine in load-bearing capacity. The findings contribute valuable insights into the optimization of CLT beam design for structural applications.